In Vitro Synergism Effect of an Aqueous Garlic Extracts against Six Commonly Clinical Isolated Candida Species - A A Jafari; A Fatahi Bafghi; MH Anvari; H Zarrinfar (Tehran University of Medical Sciences, 2007)
Background: The growth of different microorganisms including bacteria, fungi and viruses has been inhibited by garlic extracts in many studies. The antifungal activity of aqueous garlic extract was investigated in an in vitro system using broth microdilution method against six commonly clinical isolates of Candida species. The synergic antifungal effect of garlic and amphotericin B was also determined in this study. The aim of this study was to evaluate the in vitro antifungal activity of an aqueous extract of garlic against six commonly clinical Candida species isolated from patients with systemic candidiasis Methods: The yeast strains examined were clinically isolated of C. albicans, C. tropicalis, C. glabrata, C. parapsilosis, C. guillermondi and C. krusei. The minimum inhibition concentration, MIC endpoints and checkerboard titrations of garlic extracts and amphotericin B were determined using broth microdi-lution test according to National Committee for Clinical Laboratory Standards (NCCLS) document. Results: The strongest activity of garlic extracts was seen against Candida tropicalis, followed by C. glabrata, and C. albicans. The minimum inhibition concentration (MIC) of garlic extract was 0.78, 1.56, and 3.125 mg/ ml for Candida tropicalis, C. glabrata, and C. albicans respectively. C. krusei was the most resistant species against garlic extract in this study with MIC 6.25 mg/ml. The amphotericin B minimum inhibition concentration was reduced six folds against C. tropicalis, 4 folds against C. glabrata, and C. albicans, and 2 folds for other Candida strains. Conclusion: Candida tropicalis was the most sensitive tested Candida species to garlic extracts followed by C. glabrata and C. albicans. However the mechanisms of action weren't clear and more in vitro studies is necessary for determination of its growth inhibitory activity mechanisms.